Training On The Development Of Differentiated Learning Tools For Inclusion Teachers At Labschool UNESA Lidah Wetan Surabaya - Dwirisnanda, Danis Ade; Wijiastuti, Asri; Widajati, Wiwik; Nur, Devina Rahmadiani Kamaruddin; Ekasari, Diah (Lumbung Inovasi: Jurnal Pengabdian kepada Masyarakat, 2024)
Children with special needs can be interpreted as children who are slow or have disorders (retarded) who will never succeed in school for children in general. Children with special needs can also be interpreted as children who have physical, mental, intelligence and emotional disorders so that special learning is required. Children with special needs have a classification, namely physical disorders, mental disorders, behavioral disorders. Children with Special Needs (ABK) are increasingly being found day by day. ABK who appear are not only those who are slow to understand lessons slow learners, stand out / gifted or berkabat, but also those who are hyperactive, autistic and other types of ABK. The importance of handling students in the ABK category is very necessary because the success of basic education is very important for students to be able to continue their education at the next level, therefore, teachers in schools need to be given insight, introduction and training about ABK knowledge and methods of handling it. Currently, the Labschool Unesa Lidah Wetan neighborhood school has 9 students with special needs spread across elementary school levels, at school they are served by class teachers and several parents who accompany them while studying. Their disorders tend to be autism and lack of focus. Class teachers and parents of students do not yet have adequate knowledge about special needs, therefore knowledge and understanding of handling special needs are needed so that teachers and parents can work together in providing services, so that they will provide optimal results. This training was conducted for representatives of the inclusive teachers of the Labschool Unesa Lidah Wetan neighborhood school, totaling 16 people. This training activity aims to equip inclusive teachers in handling children with special needs. This training is given to inclusive teachers with special needs students who really need special attention and treatment. The training is conducted in the form of workshops or seminars with theory and practice provided in a balanced manner. Implementation in the classroom will be monitored by the PKM team. The results will be analyzed by describing the implementation of the training results in the field, as well as describing changes in handling special needs students.